Electrochemical Measurements Reveal Reactive Oxygen Species in Stress Granules. Issue 28 (9th June 2021) - Hu, Keke; Relton, Emily; Locker, Nicolas; Phan, Nhu T. N.; Ewing, Andrew G.
Abstract: Stress granules (SGs) are membrane‐less organelles that assemble in the cytoplasm to organize cellular contents and promote rapid adaptation during stress. To understand how SGs contribute to physiological functions, we used electrochemical measurements to detect electroactive species in SGs. With amperometry, we discovered that reactive oxygen species (ROS) are encapsulated inside arsenite‐induced SGs, and H2 O2 is the main species. The release kinetics of H2 O2 from single SGs and the number of H2 O2 molecules were quantified. The discovery that SGs contain ROS implicates them as communicators of the cellular stresses rather than a simple endpoint. This may explain how SGs regulate cellular metabolism and stress responses. This may also help better understand their cytoprotective functions in pathological conditions associated with SGs such as neurodegenerative diseases (NDs), cancers and viral infections. Abstract : Arsenite‐induced stress granules isolated from both non‐cancer and cancer cells contain reactive oxygen species as revealed by amperometric measurements with Pt or platinized carbon microelectrodes. This finding supports a role for SGs as signaling hubs and unveils a correlation between SG biology and pathogenesis in neurodegenerative diseases and some cancers.